Analysis of TikTok Account @VinaMuliana as a Media for Young Generation Career Education in the Digital Era - Hidayatullah, Wiyanto; Magfirah, Noor Khalida; Elviria, Samia (Universitas Tribhuwana Tungga Dewi, 2025)
This study aims to explore the use of TikTok as a career education medium, with a focus on the TikTok account @vnmuliana. The purpose of this study is to assess the effectiveness of TikTok as a career-related information platform, especially for the younger generation. This study uses a descriptive method with data collection through interviews and observations of the content of the @vnmuliana account from 2021 to the present. The results showed that TikTok, with a large number of users in Indonesia, is an effective tool for disseminating career education. The content shared by @vnmuliana, including job interview tips, CV preparation, and career opportunity information, has a significant impact on young audiences, as evidenced by positive testimonials about career advancement and skills improvement. Using Laswell's Communication Model and the SMART framework, this study highlights how @vnmuliana's career education content is specific, measurable, achievable, realistic, and time-bound. This study concludes that TikTok is a valuable platform for career education, providing wide reach and interactive content. It is recommended that educators and other career professionals consider using social media platforms such as TikTok to engage young people and improve career readiness.Penelitian ini bertujuan untuk mengeksplorasi pemanfaatan TikTok sebagai media pendidikan karier, dengan fokus pada akun TikTok @vnmuliana. Tujuan penelitian ini adalah untuk menilai efektivitas TikTok sebagai platform informasi terkait karier, terutama untuk generasi muda. Penelitian ini menggunakan metode deskriptif dengan pengumpulan data melalui wawancara dan observasi terhadap konten akun @vnmuliana dari tahun 2021 hingga saat ini. Hasil penelitian menunjukkan bahwa TikTok, dengan jumlah pengguna yang besar di Indonesia, merupakan alat yang efektif untuk menyebarkan pendidikan karier. Konten yang dibagikan oleh @vnmuliana, termasuk tips wawancara kerja, persiapan CV, dan informasi peluang karier, memiliki dampak signifikan pada audiens muda, terbukti dari testimoni positif tentang kemajuan karier dan peningkatan keterampilan. Dengan menggunakan Model Komunikasi Laswell dan kerangka SMART, penelitian ini menyoroti bagaimana konten pendidikan karier @vnmuliana spesifik, terukur, dapat dicapai, realistis, dan terikat waktu. Penelitian ini menyimpulkan bahwa TikTok adalah platform yang berharga untuk pendidikan karier, memberikan jangkauan luas dan konten interaktif. Disarankan agar pendidik dan profesional karier lain mempertimbangkan untuk menggunakan platform media sosial seperti TikTok untuk melibatkan generasi muda dan meningkatkan kesiapan karier.